The survival of contrastive analysis hypothesis: Reevaluates criticisms and highlights its value in cross-cultural communication studies - Sueda Erzin (Journal of Language, Literature, Social and Cultural Studies, 2026)
Contrastive Analysis Hypothesis (CAH) has long been an important tool in understanding the relationship between the first language (L1) and the second language (L2). CAH can be traced to its origins: the behaviorist theory, whose primary role was to predict linguistic interference. However, since this hypothesis has been criticized for not being inclusive and sensitive about learner errors, it left the spotlight to Error Analysis and Interlanguage Theory. However, this systematic review of 19 empirical articles sourced from the Web of Science (2016–2025) reveals that CAH remains highly relevant. Current research demonstrates a paradigm shift: it is not only used as a tool to identify errors, but it also helps educators foster linguistic awareness and bridge the gap between L1 and target-language structures. The study concludes that CAH is a prominent tool, despite previous criticisms, and can be a practical way to enhance both teaching methodologies and learner outcomes when applied in a balanced manner.